The first clinical experience in prostate cancer salvage cryotherapy - Ulys, Albertas; Vėželis, Alvydas; Snicorius, Marius; Anglickis, Marius (Acta medica Lituanica, 2014)
Introduction. Prostate cancer is the most common malignant neoplasia among men in Lithuania, though it presents a low mortality rate. In 2007 more than 3 500 Lithuanians were diagnosed with prostate cancer. Many patients were treated with radiotherapy. Unfortunately, after several years the number of cases of prostate cancer recurrence after radiotherapy started to grow. This new problem requires the following difficult decision to make: which treatment method to choose? Radical prostatectomy, high-dose radiotherapy, cryotherapy, high-intensityfocused ultrasound, active surveillance or hormone therapy – all are viable salvage methods. In 2012 we performed the first cryotherapy procedures. Now we want to present our first clinical experience in prostate cancer salvage cryotherapy. Materials and methods. Five patients diagnosed with prostate cancer were selected for prostate cryotherapy. Four patients were treated only with radiotherapy, one patient was treated with radiotherapy plus neoadjuvant hormonal treatment. Prostate cancer recurrences were diagnosed by multiparametric MRI and ultrasound guided transrectal or transperineal biopsies. MRI findings were validated with the Magnetic Resonance Prostate Imaging Reporting and Data System (PI-RADS). CT, MRI, ultrasound scanning, and bone scintigraphy were performed for patients before treatment. No pathological bone changes were detected. All patients received 2-cycle cryotherapy with real-time ultrasound guidance and temperature change tracking. Results. The described treatment scheme for these patients enables to deliver two freezing-thawing cycles with 10–12 probes and a urethra-warming catheter. All procedures were completed succesfully without any intraoperative complications. Urinal obstruction was observed after 1 week for 1 of 5 patients. He had to stay with epicystostomy and overwent prostate transurethral resection. After these procedures the patient could urinate normally. One patient had biochemical progression due to metastasis in parailiacal lymph nodes, and he got external beam therapy to lymph-node projection. After 6 months there was no cancer progresion signs on MRI and PSA was 1.77 ng/ml. No patients suffered from urinary incontinence. Conclusions. Our initial experience shows that cryotherapy can be a viable alternative for patients with disease progression after radiotherapy. Currently the biggest advantages of cryotherapy are as follows: possibility to treat patients not suitable for salvage prostatectomy, short hospitalization, low complication risk and lower overall cost than other methods. Short term data seems to be promising but longer follow-up is necessary to verify oncological and functional results.
Keywords: prostate cancer; recurrence; cryotherapy; salvage cryotherapy